The s-Parameter on the Transform Integrals is a Constant - Evangelista Jr., Armando (Zenodo, 2019)
The proposition of this paper is simple: the s-parameter on any transform integral is a constant and not an independent variable. Every transform integral is a different independent system that has its own set of parameters. The integral is evaluated through all values of the independent variable such that it is constant.